Survey of Zoonotic and Non-zoonotic Vector-Borne Pathogens in Military Horses in Lisbon, Portugal - Fuehrer, Hans-Peter; Alho, Ana Margarida; Kayikci, Feodora Natalie; Shahi Barogh, Bita; Rosa, Hugo; Tomás, José; Rocha, Hugo; Harl, Josef; Madeira de Carvalho, Luís (Frontiers in Veterinary Science, 2020)
Vector-borne diseases of zoonotic and/or veterinary relevance have been increasingly reported in horses globally, although data regarding working and military horses is lacking. Portuguese military horses may constitute a risk group for these pathogens, as they frequently work outdoors in various regions of the country. This study included 101 apparently healthy horses belonging to the Portuguese National Republican Guard. Blood samples were analyzed to determine the presence and prevalence of piroplasms, Anaplasmataceae, Rickettsia spp. and filarioid helminths. Overall 32.7% of the horses gave positive results for Theileria equi. Two genotypes of T. equi were verified. No positive results were recorded for Anaplasma spp., Rickettsia spp., filarioid helminths and Babesia caballi. As equine piroplasmosis is a severe infectious tick-borne disease responsible for significant losses in equine production and with numerous impacts in the international movement of horses, adequate treatment and preventive measures are needed to reduce exposure to vectors and future infections.